Sloshing induced damping across Froude numbers in a harmonically vertically excited system. (13th October 2021) - Constantin, L.; De Courcy, J.J.; Titurus, B.; Rendall, T.C.S.; Cooper, J.E.
Abstract: An investigation was performed to measure sloshing motion and damping during harmonic forced vertical motion of a rectangular tank containing fluid, with a particular focus on the amplitude dependent transition between lateral sloshing and turbulent, vertical slamming. Qualitative and quantitative explanations are provided for the damping saturation point and dissipation effects, together with metrics to distinguish the different sloshing regimes, and a ballistic-harmonic analytical model is presented capable of reproducing the physical trends. Image processing tools were used to analyse experimental high-speed video footage, illustrating potential routes to increased damping in vertically oscillating structures, and correlating well with measured fluid forces and flow regimes. Graphical abstract: Highlights: Sloshing-induced motion and damping across Froude numbers is studied. Hysteresis cycle analysis reveals liquid motion patterns associated with damping. Amplitude dependent transition between lateral sloshing to turbulent vertical motion. Analytical ballistic model helps explain observed effects.